Efficacy of Transcutaneous Electric Nerve Stimulation (TENS) on Whole Salivary Flow Rate: A Descriptive Observational Study - Sunbul Tabrez; Neelkant Patil; Mohit Sareen; Manoj Meena; Nitesh Tyagi; Shobhit Kaswan (Shiraz University of Medical Sciences, 2022)
Statement of the Problem: Saliva is a precious oral fluid that contributes to oral health and when its quantity is diminished, it hampers the quality of life. Individuals suffering from diabetes have a complaint of reduced salivation due to the consumption of xerogenic drugs and autonomic neuropathy. Purpose: Our study aims to evaluate the effectiveness of the transcutaneous electric nerve stimulation (TENS) device on the salivary flow rate with respect to age and gender in Jaipur population. Materials and Method: A descriptive observational study was carried out on individuals in Jaipur at the Department of Oral Medicine and Radiology at Rajasthan Dental College and Hospital during a period of 7 months. The study consisted of 200 individuals who were divided into two groups. Unstimulated and stimulated saliva were collected for 5 minutes in a graduated beaker. Stimulated saliva was collected after keeping the TENS unit activated at 50Hz. Kolmogorov-Smirnov, Shapiro-Wilks normality tests and Mann Whitney U test were done. The p value <0.05 was considered to be significant. Results: The TENS unit was effective in increasing the quantity of stimulated saliva and a highly statistical significance was seen in age groups. TENS was also found to be more effective in increasing saliva in diabetic individuals. The mean unstimulated salivary rate was 1.64ml/5min and the mean stimulated salivary rate was 1.914ml/5min for Group I. The mean unstimulated salivary rate was 1.231ml/5 min and the mean stimulated salivary rate was 1.547ml/5 min for Group II. The p value for Group I and II for unstimulated saliva was 0.01 and for stimulated saliva was 0.03. Conclusion: It seems that TENS has shown positive results in increasing salivary secretions and salivary values may diminish with age; therefore, TENS might be used in aged individuals as well as in diabetic patients to increase the quantity of saliva.